Nano Online 2016
DOI: 10.1515/nano.12951_2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated myoblast differentiation on graphene oxide-impregnated PLGA-collagen hybrid fibre matrices

Abstract: Background: Electrospinning is a simple and effective method for fabricating micro-and nanofiber matrices. Electrospun fibre matrices have numerous advantages for use as tissue engineering scaffolds, such as high surface area-to-volume ratio, mass production capability and structural similarity to the natural extracellular matrix (ECM). Therefore, electrospun matrices, which are composed of biocompatible polymers and various biomaterials, have been developed as biomimetic scaffolds for the tissue engineering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 44 publications
0
45
0
Order By: Relevance
“…Figure shows the FT‐IR spectra of GO flakes, Col, and Col–GO‐90 scaffolds with the corresponding reduced sample. For GO flakes, peaks at 1054 cm −1 were related to the alkoxy group, and those at 1620 and 1728 cm −1 were both attributed to the carboxyl group (COOH) . Infra‐red spectra of the Col scaffold showed amide I, II, III, and A group peaks at 1645, 1549, 1243, and 3315 cm −1 , respectively .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure shows the FT‐IR spectra of GO flakes, Col, and Col–GO‐90 scaffolds with the corresponding reduced sample. For GO flakes, peaks at 1054 cm −1 were related to the alkoxy group, and those at 1620 and 1728 cm −1 were both attributed to the carboxyl group (COOH) . Infra‐red spectra of the Col scaffold showed amide I, II, III, and A group peaks at 1645, 1549, 1243, and 3315 cm −1 , respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, GO with concentrations of 3000 and 5000 μg/mL enhanced cell proliferation within gelatin methacryloyl matrixes . In a study by Shin et al, it was demonstrated that a GO–PLGA–Col scaffold showed no toxicity and the composite matrix with concentrations of 10,000 μg/mL also exhibited cell attachment and proliferation better than that of PLGA‐Col composites . Two recent studies showed no toxicity for Col–GO scaffolds with GO concentrations of 1000 and 2000 μg/mL .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have fabricated highly interconnected and porous graphene aerogels (Qiu et al, 2014), and other nanocomposites such as graphene with PLGA (Ahadian, Ostrovidon et al, 2013;Jun, Jeong, & Shin, 2009;Shin et al, 2015).…”
mentioning
confidence: 99%
“…163 Electrospun PLGA-collagen impregnated GO fibers were also observed to promote adhesion and proliferation of C2C12 cells. 164 In another recent study, conductive PCL-graphene composite scaffolds promoted the adhesion and proliferation of C2C12 cells, as well as inducing the differentiation of these cells into multinucleated myotubes in a concentration-dependent manner. 165 Stem cell based-treatments remain as promising strategies for cardiac regeneration, but despite the ability of MSCs to differentiate into cardiomyocytes in vitro, their clinical efficacy is quite low.…”
Section: Muscle Regenerationmentioning
confidence: 93%